1995
DOI: 10.1089/neu.1995.12.903
|View full text |Cite
|
Sign up to set email alerts
|

The Neurochemical and Metabolic Cascade Following Brain Injury: Moving from Animal Models to Man

Abstract: Experimental traumatic brain injury produces a series of cellular events contributing to a neurochemical and neurometabolic cascade. This cascade is defined by the release of neurotransmitters resulting in a massive ionic flux, which, consequently, produces an increase in glycolysis. This increase in glycolysis is followed by a metabolic diaschisis, which is related to the degree and extent of behavioral deficits. Clinical efforts have now determined that a similar cascade occurs in human head injury, validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
113
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(118 citation statements)
references
References 20 publications
5
113
0
Order By: Relevance
“…Studies of brain energy metabolism after human and rodent brain injury demonstrate dynamic changes occurring during the acute period after injury, such that a hypermetabolic state lasting only 30 minutes (in rats) to a few hours (in humans) is followed by a profound depression lasting 5-10 to 30 days in rats and humans, respectively [27,30,46]. Along the same time course, we have recently shown that NMDA glutamate receptors in mice subjected to closed head injury undergo dynamic changes in activation and availability [5], with a transient activation (less than 1 hour) followed by long lasting decrease (over seven days) in receptor function and availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of brain energy metabolism after human and rodent brain injury demonstrate dynamic changes occurring during the acute period after injury, such that a hypermetabolic state lasting only 30 minutes (in rats) to a few hours (in humans) is followed by a profound depression lasting 5-10 to 30 days in rats and humans, respectively [27,30,46]. Along the same time course, we have recently shown that NMDA glutamate receptors in mice subjected to closed head injury undergo dynamic changes in activation and availability [5], with a transient activation (less than 1 hour) followed by long lasting decrease (over seven days) in receptor function and availability.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, brain energy metabolism after injury fluctuates such that immediately after injury, a hyperactivated state lasting only 30 minutes (in rats) to a few hours (in humans) is followed by a metabolic depression lasting from 5-10 or 30 days in rats or humans, respectively [4,27,30,46]. We have recently used serial small animal PET imaging to show a profound, persistent metabolic decline following microdialysis cannula implant that began as early as 2.0 hrs after the surgery, was at its lowest point 48 hrs after the surgery and persisted for the duration of the experiment, 25 days [39].…”
Section: Introductionmentioning
confidence: 99%
“…It is known from previous studies that glucose levels are affected by changes in glucose supply from capillaries and glucose uptake into the tissue. 35 In general, glucose concentration indicates the amount of glucose available in the tissue as a reflection of plasma concentration and local blood flow in the tissue. During ischemia, impaired blood flow decreases the delivery of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the initial cerebral hypoperfusion we observed after experimental TBI induction. Later, cellular efforts to reestablish ionic gradients (Hovda et al, 1995) lead to hyperglycolysis and this may lead to hyperemia. Furthermore, gliosis begins ~24 hours after TBI (Gehrmann et al, 1995;Graham et al, 2000), and demands energy, which may in part be the reason for the recovery of CBF observed at this time point in many regions.…”
Section: From Morphology To Function -Hemodynamic Alterations After Tbimentioning
confidence: 99%